INVESTMENT ATTRACTIVENESS OF THE ECONOMY FACTORS AFFECTING INCREASE - Soibova , Madinabonu G‘anisher qizi (Educational Research in Universal Sciences, 2023)
This article analyzes the importance of investment attractiveness in the economy and the factors affecting it. In this analysis, in the process of assessing the investment environment, investment levels, investors’ views and BERI index were considered in general.